Dramaturgy of identity and K-Pop's fan community communication behaviour in Bone Regency - Wandi, Wandi; Marta, Rustono Farady; Qudratullah, Qudratullah; Yuliarti, Monika Sri; Nisa, Ainun (Jurnal Studi Komunikasi, 2025)
The Korean Wave (Hallyu) phenomenon has formed a new communication pattern among K-Pop fans in Indonesia, including the ARMY Bone community in Bone Regency. This study examined the communication behaviour of the ARMY Bone community through Erving Goffman's Dramaturgy Theory, focusing on the formation of formalist and ritualistic impressions, as well as identity dynamics through the concept of front stage and backstage. This study used a qualitative method of a phenomenological approach, with observation techniques, in-depth interviews, and documentation of seven informants selected purposively. The results of the study show that ARMY Bone's communication behaviour is formed through verbal symbols (Korean terms, BTS songs, the word ‘Borahae’) and nonverbal (dress style, dance, facial expressions) that form a collective identity and impression as loyal fans. In the public space (front stage), members present themselves according to the role of the community, while in the private space (backstage) they show a more authentic personal identity. These findings strengthened the concept of dramaturgy that social identity is formed through performative and contextual self-presentation strategies, along with the dynamics of the community and popular culture they adopt. The implications of these findings suggest that fan communities such as ARMY Bone play a role in shaping young people's social identities through symbolic communication and self-presentation strategies, while also being social spaces that support local expressions of global culture.